2017
DOI: 10.1039/c7cc00613f
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabromobisphenol A (TBBPA) exhibits specific antimicrobial activity against Gram-positive bacteria without detectable resistance

Abstract: We report here the antimicrobial ability of tetrabromobisphenol A (TBBPA) against Gram-positive bacteria without detectable resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…In the susceptibility studies, the common pathogens Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumanii, Pseudomonas aeruginosa and Escherichia coli were tested. TBBPA selectively exerted antimicrobial effects against Gram-positive bacteria, consistent with our previous findings (7). TBBPA inhibited the in vitro growth of SA and MRSA at a concentration of 4 or 2 µg/mL, respectively (Table 1).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…In the susceptibility studies, the common pathogens Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumanii, Pseudomonas aeruginosa and Escherichia coli were tested. TBBPA selectively exerted antimicrobial effects against Gram-positive bacteria, consistent with our previous findings (7). TBBPA inhibited the in vitro growth of SA and MRSA at a concentration of 4 or 2 µg/mL, respectively (Table 1).…”
supporting
confidence: 92%
“…TBBPA is used in epoxy resins to retard fire (6). Previous findings from our laboratory showing Gram-positive specific antimicrobial activity of TBBPA (7) led us to further study this activity against common pathogens, focusing on in vitro and in vivo antibacterial activity against SA. The primary objective of this study was to evaluate the use of TBBPA as a treatment for bacterial infection.…”
mentioning
confidence: 99%
“…A recent study showed that halogen substitution neighboring the phenolic hydroxyl groups of bisphenol A analogues significantly enhanced their antimicrobial activity. 7 Despite the importance of the molecular structure of organic pollutants, extracting this information can be a great challenge for substances of unknown or variable composition, complex reaction products, and biological materials (UVCBs). 8 In particular, this challenge has existed for decades for the UVCBs known as chlorinated paraffins (CPs).…”
Section: Introductionmentioning
confidence: 99%
“…[3 -15] The levels of TCBPA, TBBPA/S, and their derivatives and transformations are increasing year by year in the environment, which leads to potential environmental and human-health risks. [1,[16][17][18][19][20][21][22][23] For instance, they have been detected in umbilical-cord serum and in breast milk with concentrations up to 649.45 ng/g and 11 ng/g, respectively. [24,25] Evidence suggests that HFRs exhibit potential neurotoxicity, endocrine disruption effects on bio-organisms, and reproductive-development toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HFRs have become ubiquitous environmental contaminants and are detected frequently in various matrices, such as air, sewage sludge, sediment, soil, mankind and animal tissues [3–15] . The levels of TCBPA, TBBPA/S, and their derivatives and transformations are increasing year by year in the environment, which leads to potential environmental and human‐health risks [1,16–23] . For instance, they have been detected in umbilical‐cord serum and in breast milk with concentrations up to 649.45 ng/g and 11 ng/g, respectively [24,25] .…”
Section: Introductionmentioning
confidence: 99%